Use of ChatGPT in Building Personalisation in Business Services - Muhammad Ade Kurnia Harahap; Pilifus Junianto; Wahyuni Sri Astutik; Andriya Risdwiyanto; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
In today's digital age, personalised customer service is becoming increasingly important for businesses to maintain and improve customer satisfaction. Personalisation in business services involves the ability to provide an experience tailored to each customer's unique needs, preferences and characteristics. This research aims to explore the use of ChatGPT in building personalised business services by overcoming existing challenges. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study concluded that the use of ChatGPT in building personalised business services offers great potential to improve customer experience, operational efficiency and marketing outcomes. By leveraging ChatGPT's ability to interact in natural language, provide personalised recommendations, provide responsive customer support, and collect valuable data, businesses can create better customer experiences, build more personalised relationships, and improve their business success.